Biodegradable films from poly (lactic acid) (PLA)-chitosan-silver nanoparticles : preparation and characterization - Nur Bashirah, Azli (2013)
The biodegradable food packaging films were produced from biopolymers poly (lactic acid) (PLA), chitosan, and silver nanoparticles. The objectives of this research are to produce the biodegradable food packaging films from biopolymers poly (lactic acid) (PLA), chitosan, and silver nanoparticles and also to study the effects silver nanoparticles on the antimicrobial qualities of silver nanoparticles loaded with chitosan-PLA based films. Other objective in this research is to study the characterization in chemical, mechanical and biodegradability of biodegradable food packaging films. The characteristics of biodegradable food packaging films were evaluated by using equipments like Fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM). The film also was characterized in term of moisture content and water absorption test and also biodegradability test using soil burial degradation method. The biodegradable food packaging films based of PLA-chitosan loaded with silver nanoparticles also have antimicrobial properties towards any bacteria due to the present of silver nanoparticles that have characteristics of antifungal and antibacterial. In this study, the antimicrobial properties of the films were investigated through the antimicrobial activities by using agar disc diffusion methods and test the films with the microbial E.coli bacteria. The performance of films were optimized by manipulating the concentration of silver nanoparticles in order to obtain the biodegradable food packaging films that have high biodegradability and high qualities for food packaging application. The results shows that, the films were show positive response towards degradation process due to the weight loss within 12 days and the poly(lactic acid) (PLA) film show high resistivity towards water compared to the chitosan (CS) film. The concentration of silver nanoparticles at (23.1 % w/w SNP) shows the 100% of inhibition against Gram-negative bacterium E.coli and Gram-positive bacterium Micrococcus. Thus, it show that silver nanoparticles were successfully inhibit the bacteria grow and improve the antimicrobial properties of poly(lactic acid) (PLA)-loaded chitosan-silver nanoparticles blend films.